Are wearable insoles a validated tool for quantifying transfemoral amputee gait asymmetry?. (October 2019) - Loiret, Isabelle; Villa, Coralie; Dauriac, Boris; Bonnet, Xavier; Martinet, Noël; Paysant, Jean; Pillet, Hélène
Background: Amputee gait is known to be asymmetrical, especially during loading of the lower limb. Monitoring asymmetry could be useful in quantifying patient performance during rehabilitation. Wearable insoles can provide normal ground reaction force asymmetry in real-life conditions. Objectives: To characterize the validity of Loadsol ® insoles versus force plates in quantifying normal ground reaction force and gait asymmetry. To determine the influence walking speed has on loading asymmetry in transfemoral amputees. Study design: This is a prospective study. Methods: Six transfemoral amputees, wearing Loadsol ® insoles, walked at three self-selected speeds on force plates. Validity was assessed by comparing normal ground reaction force data from the insoles and force plates. The Absolute Symmetry Index was used to calculate gait loading asymmetry at each speed. Results: Normalized root mean square errors for the normal ground reaction forces were 6.6% (standard deviation = 2.3%) and 8.9% (standard deviation = 3.8%); correlation coefficients were 0.91 and 0.95 for the prosthetic and intact limb, respectively. The mean error for Absolute Symmetry Index parameters ranged from −2.67% to 4.35%. Loading asymmetry increased with walking speed. Conclusion: This study quantified the validity of Loadsol ® insoles in assessing loading asymmetry during gait in transfemoral amputees. The calibration protocol could be improved to better integrate it into a clinical setting. However, our results support the relevance of using such insoles during the clinical follow-up of transfemoral amputees. Clinical relevance: This is the first study to validate Loadsol ® insoles versus force plates and report on loading asymmetry during gait at three different speeds in transfemoral amputees. Loadsol ® insoles, which provide visual and audio feedback, are clinically easy to use and could have beneficial application in the amputee's rehabilitation and follow-up.